1984
DOI: 10.1136/ard.43.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of corticosteroid injection for traumatic olecranon bursitis.

Abstract: SUMMARY Forty-seven patients with traumatic olecranon bursitis were evaluated after a mean follow-up of 31 months (range 6 to 62 months). Twenty-two patients treated with bursal aspiration had delayed recovery and no complications of therapy. Twenty-five patients treated with intrabursal injection of 20 mg of triamcinolone hexacetonide had rapid recovery, usually within one week, but suffered complications such as infection (3 cases), skin atrophy (5 cases), and chronic local pain (7 cases). Since spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…Moreover, aspiration itself might cause new mechanical injury to the bursa and initiate another inflammatory process, which may explain the higher recurrence rate of nonseptic olecranon bursitis. On the contrary, compression/ NSAIDs may be chosen at ease for the treatment of nonseptic olecranon bursitis because the inflammatory process might subside with time if there is no further damage to the bursa [20]. The relatively low proportion of failed resolution (17%) at 4 weeks obtained in Group C supports the efficiency of compression/NSAIDs in the treatment of nonseptic olecranon bursitis.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Moreover, aspiration itself might cause new mechanical injury to the bursa and initiate another inflammatory process, which may explain the higher recurrence rate of nonseptic olecranon bursitis. On the contrary, compression/ NSAIDs may be chosen at ease for the treatment of nonseptic olecranon bursitis because the inflammatory process might subside with time if there is no further damage to the bursa [20]. The relatively low proportion of failed resolution (17%) at 4 weeks obtained in Group C supports the efficiency of compression/NSAIDs in the treatment of nonseptic olecranon bursitis.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, a study of this size cannot draw any inferences about safety nor can it compare the groups in terms of safety [10]. It is important to note that prior studies have amply documented the sometimes severe risks of injections and aspirations of olecranon bursae [8,17,18,20]. Based on these concerns, and on the absence of large differences among our study groups, we consider that compression bandaging and short courses of NSAIDs may be the safest approach for these patients and more invasive modalities be reserved for those patients who have failed such treatment [8,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smith et al [18] conducted the only randomized controlled trial on this treatment option and found a faster decrease in swelling and fewer re-aspirations for intrabursal methylprednisolone injections compared to oral naproxen or oral placebo in 42 male patients with NSB, which is in line with orther studies [3,23]. Although Smith et al [18] reported no complications, other authors have, including skin atrophy, chronic local pain, or infection [3,20,23].…”
Section: Discussionmentioning
confidence: 77%